2011
DOI: 10.1007/s10071-011-0455-9
|View full text |Cite
|
Sign up to set email alerts
|

Picture recognition of food by macaques (Macaca silenus)

Abstract: Pictorial representations of three-dimensional objects are often used to investigate animal cognitive abilities; however, investigators rarely evaluate whether the animals conceptualize the two-dimensional image as the object it is intended to represent. We tested for picture recognition in lion-tailed macaques by presenting five monkeys with digitized images of familiar foods on a touch screen. Monkeys viewed images of two different foods and learned that they would receive a piece of the one they touched fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 46 publications
5
32
0
Order By: Relevance
“…Our experimental design does not allow us to address the notion of equivalence, but taken together, we conclude that there certainly appears to be a correspondence in how crab-eating macaques perceive objects and their pictorial representations. This conclusion is in line with previous results in capuchin monkeys (Truppa et al, 2009) and lion-tailed macaques (Judge et al, 2012).…”
Section: Object-picture Perceptionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our experimental design does not allow us to address the notion of equivalence, but taken together, we conclude that there certainly appears to be a correspondence in how crab-eating macaques perceive objects and their pictorial representations. This conclusion is in line with previous results in capuchin monkeys (Truppa et al, 2009) and lion-tailed macaques (Judge et al, 2012).…”
Section: Object-picture Perceptionsupporting
confidence: 93%
“…Other studies have shown that transfer can often be more limited. Thus, macaque monkeys require considerable training to learn that selecting the picture of a preferred food item results in the delivery of that food as a reward (Judge et al, 2012). This study has highlighted large inter-individual differences between participant macaques, with the fastest learner requiring only about 15% of the training needed by the slowest learner to achieve criterion behavioral performance.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Important theoretical and practical questions undoubtedly remain. To what extent do infants confuse a picture with its referent rather than conceptualize the image as the object it represents (e.g., Judge et al, 2012)? Why do manipulative features such as pop-ups appear to undermine young children's learning from picture books (e.g., Tare, Chiong, Ganea, & DeLoache, 2010)?…”
Section: Discussionmentioning
confidence: 99%
“…Picture-object matching has been shown with rhesus monkeys (Bovet and Vauclair 2000). Lion-tailed macaques will choose photographs of preferred foods to receive that food (Judge et al 2012). Dogs can follow human commands presented through video projection (Pongrácz et al 2003), and many animals, including fish, reptiles, birds, sheep and non-human primates, show appropriate behaviors in response to pictures (Bovet and Vauclair 2000).…”
Section: Introductionmentioning
confidence: 98%